Ecosystem turnover in an urbanized subtropical seascape driven by climate and pollution. (December 2021) - Hong, Yuanyuan; Yasuhara, Moriaki; Iwatani, Hokuto; Chao, Anne; Harnik, Paul G.; Wei, Chih-Lin
Abstract: Natural and anthropogenic factors shape present-day benthic marine ecosystems. Understanding their combined influence on benthic communities is limited, however, by a lack of biological monitoring. Using a conservation paleobiology approach, this study establishes biological baselines and assesses the effects of natural and anthropogenic environmental change on benthic communities in an urbanized subtropical seascape. We compared subsurface ("past", covering approximately the last 50–100 years) and surface ("present", covering approximately the last 5 years) faunal assemblages in sediment grab samples in Hong Kong, one of the busiest ports and urbanized coastal areas in the world. Results show that both natural (climate, monsoon) and anthropogenic factors (metal pollution, damming) were associated with recent faunal changes (dissimilarities between subsurface and surface faunal assemblages). Changes in freshwater and sediment discharge from the Pearl River due to monsoon rains and dams produced a strong west-east gradient in the turnover of rare species. Pollution from metals resulted in the turnover of abundant and dominant species in the central part of Hong Kong. Examining these data in the context of published results from other urbanized coastal areas around the world suggests that metal pollution may be an important and understudied factor, responsible for benthic turnover in regions where pollution levels exceed thresholds for sediment toxicity.